Effect of supplementary milk feeding on growth and survival of Santa Inês lambs - Mcmanus, Concepta Margaret; Gomes, Edgard Franco; Paim, Tiago Prado; Louvandini, Helder; Dallago, Bruno; Borges, Barbara Oliveira [UNESP]; Zorzan, Aline; Lima, Paulo de Mello Tavares (Universidade Federal de Goiás, 2014)
The objective of this experiment was to evaluate the effect of alternative methods of feeding on the performance and mortality rate of suckling lambs. Eighty-four Santa Inês lambs, twins and singles, half male and half female, were used. The animals were divided into three groups: A (control), B (bovine milk) and C (bovine milk plus Multi-mixture). The experiment began when lambs were three weeks old and finished at weaning at 2 months of age. Each animal from group B received 200 mL of bovine milk daily; group C received 200 mL of bovine milk plus 20g of Multi-mixture daily. Weaning Weight (WW) was 10.90, 13.20 and 13.59 kg, respectively for groups A, B and C. Daily Weight Gain (DWG) was 126, 163 and 168 g.day-1 respectively. The mortality rate was higher (p<0.05) in group A than in group B and C. Gender influenced significantly (p<0.05) the DWG and WW. DWG and WW were lower for the animals that died compared to the animals that survived: 7.94 kg against 13.51 kg (WW) and 77 g against 165 g (DWG) respectively. The twins had lower (P<0.05) WW and DWG when compared to the singles. The use of milk-replacers with or without Multi-mixture is effective and it can increase the productivity of the system.

Objetivou-se com este experimento avaliar os efeitos de métodos alternativos de suplementação de cordeiros em aleitamento sobre seu desempenho e sobrevivência. Foram utilizados 84 cordeiros Santa Inês, 50 % machos e 50 % fêmeas, de partos simples e gemelares. Os animais foram divididos em três tratamentos: A (controle), B (200 mL de leite de vaca/animal/dia) e C (200 mL de leite de vaca, mais 20g de mistura múltipla/animal/dia). O experimento se inciou às três semanas de idade dos cordeiros e terminou ao desmame (2 meses). O peso dos ovinos ao desmame (PD) foi 10,90, 13,20 e 13,59 kg, para os tratamentos A, B e C respectivamente, e o ganho médio diário (GMD) foi de 126, 163 e 168 g/animal/dia, respectivamente. A taxa de mortalidade foi maior (P< 0,05) no grupo A em relação aos grupos B e C. O sexo dos animais influenciou significativaente (P<0,05) o GMD e PD. GMD e PD foram menores para os ovinos que morreram em comparação aos que sobreviveram: 7,94 kg contra 13,51 kg e 77 g contra 165g, respectivamente. Os gêmeos apresentaram GMD e PD menores (P<0,05) que os de parto simples. A suplementação com ou sem a mistura múltipla se mostrou eficiente, podendo aumentar a produtividade do sistema de produção.
Efeito da suplementação láctea sobre o crescimento e sobrevivência de cordeiros Santa Inês
Keywords: Cassava leaf|Legg shell; Mortality; Weight gain; Casca de ovo; Folha de mandioca; Ganho de peso; Mortalidade